Manual de procesos para mejorar la productividad del sector lácteo de la parroquia de Aloasí, del cantón Mejía - Vaca Padilla, Marisol Alexandra (2015)
In the present research work aims to design a process manual to improve dairy sector production on Aloasí parish, Mejia canton; for which the research methodology was qualitative and quantitative, allowing the use of techniques and data collection instruments like observation sheet, interviews aimed to many factories in the sector were dedicated to the production of dairy products, giving solution to this with the value chain of input suppliers, building production processes for each one product, creation of respective flowcharts, establishing specifications to INEN standards….